3D Printing of Gelatine/Alginate/β‐Tricalcium Phosphate Composite Constructs for Bone Tissue Engineering. Issue 41 (4th November 2019) - Kalkandelen, Cevriye; Ulag, Songul; Ozbek, Burak; Eroglu, Gunes O.; Ozerkan, Dilsad; Kuruca, Serap E.; Oktar, Faik N.; Sengor, Mustafa; Gunduz, Oguzhan
Abstract: Bone tissue engineering studies have brought three‐dimensional scaffolds into focus that can provide tissue regeneration with designed porosity and strengthened structure. Current research has concentrated on the fabrication of natural and synthetic polymer‐based complex structures that closely mimic biological tissues due to their superior biocompatibility and biodegradabilities. Gelatine/Sodium Alginate hydrogels reinforced with different concentrations of β‐Tricalcium Phosphate (TCP) (10, 13, and 15 wt.%) were studied to form 3D bone tissue. Physical, mechanical, chemical, morphological properties and biodegradability of the constructs were investigated. Furthermore, in vitro biological assay with human osteosarcoma cell line (SAOS‐2) was performed to determine the biocompatibility of the constructs. It is found that cell viability rates for all constructs were increased and maximum cell viability rate was attained for 20%Gelatine/2%Alginate/10%TCP (wt.). The present work demonstrates that 3D printed Gelatine/Alginate/TCP constructs with porous structures are potential candidates for bone tissue engineering applications. Abstract : The study entitled "3D Printing of Gelatine/Alginate/β‐Tricalcium Phosphate Composite Constructs for Bone Tissue Engineering" presented an effort to 3D‐print a gelatin‐alginate‐ β‐Tricalcium Phosphate (TCP) formulation. TCP was combined with biodegradable and biocompatible polymers to get a bone scaffold. The effects of TCP concentration on characteristic properties of the scaffolds were examined in detail.